PENGARUH FASILITAS KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA YANG DIMODERASI OLEH GAYA KEPEMIMPINAN DI HOTEL YUAN GARDEN PASAR BARU - Yosi Hana Fibri; Abrian, Youmil; Fansurya, Alfi Husni (Universitas Lancang Kuning, 2023)
Employee job satisfaction is a positive emotion that employees do to do work according to company rules, and how happy they are to receive what is given by the company based on the value they get for work experience. This study identified prior job satisfaction work facilities and compensation and then moderated by leadership style. Work facilities are facilities and infrastructure provided by the company for use by employees to support employee productivity. Compensation is something that is both financial and non-financial that employees receive as remuneration for their work. Leadership style is a way or behavior of superiors to influence subordinates. The purpose of this study was to examine the extent to which the influence of work facilities and sensitivity to job satisfaction is moderated by leadership style at Yuan Garden Hotel Pasar Baru. This research is included in the quantitative research with a causal associative approach. The sampling method is a saturated sample technique of 77 employees. Smart PLS analysis was used to evaluate the hypothesized models statistically using Smart PLS 3 software. This research shows that work facilities and recovery each positively affect job satisfaction significantly. Then leadership style as a moderating variable shows positive and significant moderating results.